A STUDY OF SCRAMBLE METHOD IN TEACHING ENGLISH FOR SECONDARY STUDENT’S WRITING SKILL - suci ariani (Journal of Education, Linguistics, Literature and Language Teaching, 2021)
In Indonesia secondary school, students are equipped with any English subject to arrange their own writing. In this case, writing is the one of difficult English skill for students. Because of that, to increase students writing skill teacher need a certain method in teaching writing. Based on student’s ability in writing that also suitable with their grades, they were difficult to arrange the sentence to be good paragraph. To solve these problem several teachers had applied a method that called scramble sentence method. This study used qualitative research method with concept analysis method or library research. The data of this study came from eight articles related about scramble method to secondary student’s writing skill. Data had analyzed from reading, reviewing, supporting and contra journal article and concluding. As the result, according to eight articles, the researcher found that scramble method was effective to increased student’s writing skill. Based on the implementation of each articles, scramble method helped students to write. It proven by the improvement of several writing aspects, such as topic sentence, supporting sentence, coherence, organization, generic structures, grammar, vocabulary, content, discourse, syntax, mechanic and language use. From the analysis, the research question of this study had answered. Keyword : Scramble method, writing, library research